2017
DOI: 10.1016/j.radi.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Development of a phantom to test fully automated breast density software – A work in progress

Abstract: We are the first group to have produced deformable phantoms that are recognized as breasts by Volpara software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Our results on the association of breast compression parameters and fibroglandular volume and volumetric breast density are in line with results from previous studies (124,125,(152)(153)(154)(155).…”
Section: The Associations Between Breast Compression Parameters and Fsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results on the association of breast compression parameters and fibroglandular volume and volumetric breast density are in line with results from previous studies (124,125,(152)(153)(154)(155).…”
Section: The Associations Between Breast Compression Parameters and Fsupporting
confidence: 93%
“…High BMI is associated with low percent mammographic density (23,116) and less favorable histopathologic tumor characteristics, including tumor size and histologic grade (180,181 (99,154). A study describing the development of a phantom to test the software showed that application of compression force and reducing the phantom thickness caused both reduction and increase in phantom's volumetric breast density estimates (155). The In Study III, to calculate BMI (one of the adjustment variables) we used information on selfreported weight and height.…”
Section: Confoundingmentioning
confidence: 99%
“…Both studies used the same automated software as used in our study. In the study describing the development of a phantom to test an automated software for density assessment, it was assumed that application of compression force and reducing the phantom thickness caused both reduction and increase in phantom's percent dense volume [27]. These findings might indicate that the radiographers, who set values of compression force, could influence the estimates of percent dense volume by applying less or more compression force.…”
Section: Discussionmentioning
confidence: 99%